Effects of experimental intracerebroventricular injection of Amylois Beta Peptide (1-42) on tha daily Bax and Bcl-2 expression en the rat hippocampus - Alfaro, Mauro (2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder marked by cognitive and behavioral impairment. The accumulations of amyloid-β (Aβ) peptides in the brain are believed to be associated with perturbations of synaptic function leading to cognitive deficits. The proto-oncogene Bax (Bcl-2-associated X protein) and related protein Bcl-2 (B-cell chronic lymphocytic leukemia/lymphoma-2) genes are triggers of apoptosis in Alzheimer’s disease (AD). Besides the cognitive deficit, AD patients also show alterations in their circadian rhythms. The objective of this study was to investigate the effects of an intracerebroventricular (i.c.v.) injection of amyloid beta peptide (1-42) on daily patterns of Bax and Bcl-2 expression, as well as of clock proteins in the hippocampus and on temporal profiles of cognitive performance of four-month-old males Holtzman rats. Groups were defined as: control (CO) and Aβ-injected (Aβ). Rats were maintained under 12 h-light:12 h-dark conditions and received food and water ad libitum throughout the entire experimental. Daily rhythms of Bax and Bcl-2 expression were analyzed by RT-PCR and protein levels by Western blots, in hippocampus samples isolated every 4 h during a 24 h period. Regulatory regions of Bax and Bcl-2 were scanned for E-box sites. The Novel Object Recognition (NOR) test was used to evaluate cognition, particularly recognition memory. We found E-box sites on regulatory regions of Bax and Bcl-2 genes, which display a daily oscillation of expression in the rat hippocampus. The i.c.v. injection of Aβ (1-42) modified daily variation of Bax and Bcl-2, and clock proteins. It was observed that the group injected with Aβ explored the novel object for less time compared to the control group, during the day and night periods. Thus, elevated Aβ peptide levels might affect the temporal patterns of cognitive function and apoptotic genes, probably by altering daily rhythms of clock proteins.